ANALISIS FILM ANIMASI UPIN DAN IPIN DALAM PENERAPAN PROKES MELALUI PERILAKU HIDUP BERSIH DAN SEHAT - Norma Yanti; Mei Fita Asri Untari; Rofian (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research was motivated by the implementation of health protocols through clean and healthy living behaviors of children at SDN Karangasem which have not been maximized. The focus of this study is how the analysis of the upin and Ipin episode 16 animated film "Guna Masker Really" in the application of the prokes to avoid Covid-19 through clean and healthy living behaviors and how to apply the prokes to avoid Covid-19 through clean and healthy living behaviors of grade III students of SDN Karangasem Mranggen The purpose of this study is to analyze the upin animated film and ipin episodes of “Guna Masker Really” in the application of the prokes to avoid covid-19 through clean and healthy living behavior of grade III students of SDN Karangasem. This type of research is qualitative. Data collection techniques are: (1) Interviews; (2) Observation; and (3) Documentation. Based on the results of the study, data were obtained that the implementation of health protocols through clean and healthy living behaviors of grade III students showed good results judging from the results of observations and interviews. This shows that the animated film Upin and Ipin episode “Guna Masker Really” can be used as a means of learning health protocols through the application of clean and healthy living behaviors because the episode contains many messages about healthy living during a pandemic that children can imitate.